The wonderful story of henry sugar - Dahl, Roald (Puffin Books, London, 1977)
This collection of stories includes "The Boy Who Talked With Animals", "The Hitch-hiker", "The Mildenhall Treasure", "The Swan", "The Wonderful Story of Henry Sugar", "Lucky Break" and "A Piece of Cake".